O atendimento pedagógico domiciliar: uma experiência de implantação no sertão da Bahia, para crianças com paralisia cerebral - Machado, Patrícia Mara dos Santos (2017)
The present work reflects on the pioneer experience of pedagogical homecare developed in Feira de Santana, backwoods of Bahia, and the restraints to setting it up, on Special Education point of view. This dissertation is the result of pedagogical experience on child with cerebral palsy, not allowed to attend a regular school because of health problems, opening a new path not already taken. At this point, on this dissertation, I have as a goal to analyze the process of appliance of this kind of care, pointing out the paths taken on the process of child scholarship. From this perspective, I report the implication of different sectors of society, searching for an efficient and successful educational care for everyone in need. On this opportunity, we bring up legal and pedagogical aspects, examining official documents which directs this unique experience, pointing out the implementation of educational law for everyone, on municipal department of education. Basing this research on educational care, which emerges from intentions to offer a good quality scholarship for this new demand, purposing a human care for every person involved, I use as reference, authors such as Sacristán, Rousseau, Tomaz Tadeu da Silva, Paulo Freire and so on